Community Empowerment with Sustainable Development Goals Program Through Blue Pea Flower Processing in Wonosari Village, Gondangrejo, Karanganyar Regency - Ningsih, Novia Wahyu; Al Imama, Nur Hasanah; Amal, Nur Ikhlasul; Lestari, Putri; Zuraida, Qonita Binti; Sukamto, Rachma Regita; Novizina, Rehan Husina; Ristiyani, Rinda; Nugraheni, Risa Atitka; Putra, Rudfiando Ikhsana; Jariono, Gatot (Universitas Muhammadiyah Surakarta, 2022)
Wonosari Village is a village located in Gondangrejo, Karanganyar Regency, Central Java. This village has several potentials that can be utilized and developed. Community Service Institute and Organizational Development Universitas Muhammadiyah Surakarta (LPMPP UMS) through Thematic Real Work Lectures (Thematic KKN) has tried to reduce and provide solutions to the problems faced by villages and their communities in this village. This Thematic KKN is carried out over a period of three months, and it is part of the 2022 Independent Campus Competition Program (PKKM). One of the programs that has been carried out in this village is Blue Pea Flower Processing. This program was well implemented and involved various partners, such as village officials, youth organizations and village communities.